Associations between negative gender attitudes and eating behaviors in Chinese children and adolescents - Cao, Ruiyao; Chen, Jiaoyan; Wang, Yuanyuan; Peng, Xingwang; Han, Mei; Liu, Keke; Zhang, Juan; Yao, Rongying; Han, Hui; Fu, Lianguo (Frontiers in Nutrition, 2023)
Background: Negative gender cognitive attitudes (disliking one’s own gender or wanting to be the opposite gender) and unhealthy eating behaviors have become common in Chinese children and adolescents. The aim of this study was to analyze the associations between negative gender attitudes and eating behaviors among Chinese children and adolescents. Methods: Primary and secondary school students aged 8-15 years were selected as participants using a stratified cluster random sampling method. The self-designed questionnaire was used to investigate the participants’ negative gender cognitive attitudes. Eating frequency questionnaire was used to investigate participants’ eating behaviors. Under the leading reading of standardized training investigators, the questionnaire for children aged 8-15 years was completed by themselves in the form of centralized filling. Results: A total of 6.5% (43/657, boys: 6.1% (21/347), girls: 7.1% (22/310)) of children disliked their own gender, 8.8% (58/657, boys: 5.5% (19/347), girls: 12.6% (39/310)) of children wanted to be of the opposite gender, and the proportion of girls with negative gender attitudes was higher than that of boys (P < 0.05). Boys who disliked their own gender or wanted to be the opposite gender had higher frequencies of unhealthy eating behaviors and lower frequencies of healthy eating behaviors than boys who liked their own gender or did not want to be the opposite gender (P < 0.05). Girls who disliked their own gender or wanted to be the opposite gender had higher frequencies of protein eating behaviors than girls who liked their own gender or did not want to be the opposite gender (P < 0.05). There was a significant interaction between disliking one’s own gender and wanting to be the opposite gender in midnight snack eating among boys (P < 0.05) and in carbonated drink and high protein eating behaviors among girls (P < 0.05). Conclusion: Boys with negative gender cognitive attitudes express more unhealthy eating behaviors and fewer healthy eating behaviors; Girls with negative gender cognitive attitudes exhibit more protein eating behaviors.